Problem Pengajaran Sastra di SMK - Teguh Trianton (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
At high-school vocational education, literary lesson didn’t have yang proper portion. This is a serious problem, if education wishes to build nation character by humanizing human. The problem at vocational education is, at its 2004’s curriculum that Indonesian language lesson fully directed to one direction, namely using utilizing right and roper Indonesian language to communicate at work. Therefore, it’s the time for government and education department to reformulate or revitalize the real education goal, by equalizing all matters and lesson even if that lesson didn’t tested at national test (UN). Teacher also must apply curriculum with flexibility and wise, because curriculum inst a sacred text that annul interpretation and difference on its realization.